Green and Facile Synthesis of Metal-Organic Framework Cu-BTC-Supported Sn (II)-Substituted Keggin Heteropoly Composites as an Esterification Nanocatalyst for Biodiesel Production - Zhang, Qiuyun; Ling, Dan; Lei, Dandan; Wang, Jialu; Liu, Xiaofang; Zhang, Yutao; Ma, Peihua (Frontiers in Chemistry, 2020)
In the present study, metal-organic framework Cu-BTC supported Sn (II)-substituted Keggin heteropoly nanocomposite (Sn1.5PW/Cu-BTC) was successfully prepared by simple impregnation method and applied as a novel nanocatalyst for producing biodiesel from oleic acid (OA) through esterification. The nanocatalyst was characterized by Fourier transform infrared spectrometer (FTIR), wide-angle X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscope (TEM), nitrogen adsorption-desorption, thermogravimetric (TG), and NH3-temperature-programmed desorption (NH3-TPD). Accordingly, the synthesized nanocatalyst with a Sn1.5PW / Cu-BTC weight ratio of 1 exhibited the relatively large specific surface area, appropriate pore size, and high acidity. Moreover, the OA conversion of 87.7% was achieved under optimum reaction conditions. The nanocatalyst was reused seven times, and the OA conversion maintained more than 80% after three times. Kinetic study showed that the esterification reaction followed first-order kinetics and the activation energy (Ea) was calculated to be 38.3 kJ/mol.